Perspectives on Tobacco Product Waste: A Survey of Framework Convention Alliance Members’ Knowledge, Attitudes, and Beliefs - Javadian, Sanas (Int J Environ Res Public Health, 2015)
Cigarette butts (tobacco product waste (TPW)) are the single most collected item in environmental trash cleanups worldwide. This brief descriptive study used an online survey tool (Survey Monkey) to assess knowledge, attitudes, and beliefs among individuals representing the Framework Convention Alliance (FCA) about this issue. The FCA has about 350 members, including mainly non-governmental tobacco control advocacy groups that support implementation of the World Health Organization’s (WHO) Framework Convention on Tobacco Control (FCTC). Although the response rate (28%) was low, respondents represented countries from all six WHO regions. The majority (62%) have heard the term TPW, and nearly all (99%) considered TPW as an environmental harm. Most (77%) indicated that the tobacco industry should be responsible for TPW mitigation, and 72% felt that smokers should also be held responsible. This baseline information may inform future international discussions by the FCTC Conference of the Parties (COP) regarding environmental policies that may be addressed within FCTC obligations. Additional research is planned regarding the entire lifecycle of tobacco’s impact on the environment.